2015
DOI: 10.4172/2155-9899.1000311
|View full text |Cite
|
Sign up to set email alerts
|

Macrophage Polarization in Virus-Host Interactions

Abstract: Macrophage involvement in viral infections and antiviral states is common. However, this involvement has not been well-studied in the paradigm of macrophage polarization, which typically has been categorized by the dichotomy of classical (M1) and alternative (M2) statuses. Recent studies have revealed the complexity of macrophage polarization in response to various cellular mediators and exogenous stimuli by adopting a multipolar view to revisit the differential process of macrophages, especially those re-pola… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
37
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(37 citation statements)
references
References 122 publications
0
37
0
Order By: Relevance
“…However, when M1-type cells were infected 48 hr after polarization in the present study, no inhibitory effects on PRRSV replication were observed. To some extent, the phenotype of polarized M1-M2 macrophages can be reversed in vitro and in vivo [ 12 , 28 ]. Indeed, our unpublished data demonstrated that M0-/M1-type PAMs were re-polarized to the M2 type as a result of HP-PRRSV infection.…”
Section: Discussionmentioning
confidence: 99%
“…However, when M1-type cells were infected 48 hr after polarization in the present study, no inhibitory effects on PRRSV replication were observed. To some extent, the phenotype of polarized M1-M2 macrophages can be reversed in vitro and in vivo [ 12 , 28 ]. Indeed, our unpublished data demonstrated that M0-/M1-type PAMs were re-polarized to the M2 type as a result of HP-PRRSV infection.…”
Section: Discussionmentioning
confidence: 99%
“…Although macrophage adaptability provides a selective advantage in host resistance to pathogen, this same plasticity can sometimes be exploited and subverted by pathogens to invade the host. Indeed, in mammals, it is not infrequent in an infectious disease setting to find pathology associated with dynamic changes in macrophage activation, where M1 macrophages are associated with initiating and sustaining inflammation and M2 macrophages are associated with either resolution or chronic infection (Cassetta et al 2011; Herbein and Varin 2010; Labonte et al 2014; Sang et al 2015; Shaked et al 2014). Interestingly, in mouse models, the polarized M1/M2 phenotypes can, to some extent, be experimentally reversed in vitro and in vivo, which makes macrophages interesting targets for immune-modulation and therapeutic applications (Guiducci et al 2005; Saccani et al 2006).…”
Section: 1 Introductionmentioning
confidence: 99%
“…Viral infections can drive M1 polarization that in turn enhances antiviral immunity. IFN-1 plays a role in M1 polarization of macrophages exposed to virus infection (Sang et al, 2015). Accordingly, IFN-1 concentration was detectable in the media of macrophages infected by the Maraba virus (Figure 2B).…”
Section: Discussionmentioning
confidence: 88%